The dimethylhydrazine induced colorectal tumours in rat - experimental colorectal carcinogenesis - Perše, Martina (Radiology and oncology (Ljubljana), 2005)
Animal models of colorectal carcinogenesis represent invaluable research tool for investigating colorectal cancer (CRC). Experimentally induced tumours in laboratory animals provide opportunity for studying certain aspects of tumoursthat cannot be effectively studied in humans. Significant information on human CRC aetiology or factors influencing it has derived from studies using dimethylhydrazine (DMH) model that is one of the experimental models appreciated for its morphological similarity to human CRC. Today, DMH model represents useful research tool for the studies of colon carcinogens and chemopreventive agents. The review offers insight into morphogenesis and genetic alterations of DMH induced colorectal epithelial tumours in rats.
Keywords: Adenocarcinoma; Adenokarcinom; Adenom; Adenoma; Bolezen, živalski modeli; Chemically Induced; Colorectal Neoplasms; črevesje; Dimethylhydrazines; Dimetilhidrazini; Disease Models, Animal; Kolorektalne novotvorbe; Miši seva F344; Pathology; podgane; Podgane, Sprague-Dawley; Podgane, Wistar; poskusi; rak (medicina); Rats, Inbred F344; Rats, Sprague-Dawley; Rats, Wistar